Reliability and validity of the chronic respiratory questionnaire (CRQ). - Wijkstra, P. J. (1994)
BACKGROUND--The Chronic Respiratory Questionnaire (CRQ) is frequently applied to assess quality of life in patients with chronic obstructive pulmonary disease (COPD). However, the reliability and validity of this questionnaire have not yet been determined. This study investigates the reliability and validity of the four separate dimensions of the CRQ. METHODS--The CRQ was administered on two consecutive days to 40 patients with COPD (mean FEV1 44% predicted, FEV1/IVC 37% predicted). Internal consistency reliability of each dimension was investigated by Cronbach's alpha reliability coefficient, test retest reliability by the Spearman-Brown reliability coefficient (p), and content validity by Pearson's correlation coefficient between the CRQ and the symptom checklist (SCL-90). RESULTS--Items of the fatigue, emotion, and mastery dimensions showed a high internal consistency reliability (alpha = 0.71-0.88) as well as a high test retest reliability (p above 0.90). These three dimensions correlated with comparable dimensions of the SCL-90. Items of the dyspnoea dimension showed a low internal consistency reliability (alpha = 0.53) and a test retest reliability of p = 0.73. CONCLUSIONS--Items of the dimensions fatigue, emotion, and mastery of the CRQ are reliable and valid and can be used to assess quality of life in patients with severe airways obstruction. Items of the dyspnoea dimension are less reliable and should not be included in the overall score of the CRQ in comparative research. However, by scoring the items of dyspnoea separately they may be useful for the evaluation of the effects of intervention in a specific patient.